Floristic composition and stand structure of mangrove forests with varying vegetation conditions in Sungai Apit, Siak, Riau, Indonesia - Siti Fatonah; RASOEL HAMIDY; ARAS MULYADI; EFRIYELDI EFRIYELDI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Fatonah, Hamidy R, Mulyadi A, Efriyeldi. 2021. Floristic composition and stand structure of mangrove forests with varying vegetation conditions in Sungai Apit, Siak, Riau, Indonesia. Biodiversitas 22: 3972-3983. Mangrove forest in Sungai Apit Sub-district, Siak District, Riau is one of mangrove ecosystems that is still partly natural with some parts being damaged or rehabilitated. Degraded mangrove forest is a mangrove forest that has been disturbed by human activities and natural factors. This study aimed to investigate the floristic composition and stand structure of trees and seedlings in mangrove forests in Sungai Apit, Siak District, Riau Province, Indonesia in three vegetation conditions, i.e., natural, degraded, and rehabilitated forests. Line Transect Plot Method was used to collect data in three stations (i.e., Rawa Mekar Jaya, Sungai Rawa and Mengkapan villages) where each station consisted of three transects with a size of 10 x 100 m. A total of 20 species belonging 11 families were recorded in the studied sites with Rhizophora apiculata was the most dominant species in all forest conditions. The natural forest had the highest number of species followed by rehabilitated forest and the degraded forest. Stand structure in terms of tree density, mean diameter of mangrove trunks, and basal area differed significantly across the three vegetation conditions with the natural forest had the highest values followed by the rehabilitated forest, while the degraded forest was the lowest. For the seedling, the lowest number of species was observed in the degraded forest while the highest was in the rehabilitated forest, indicating the result of rehabilitation activities. Yet, seedling density in natural forests was lower than that in rehabilitated and degraded forests. This study provides information that differences in structure, species composition and recruitment of seedlings in mangrove forests in the three conditions and locations can be related to differences in recovery time and degradation levels which may be important for developing mangrove forest management and conservation strategies.